Mortality risk by peak serum creatinine in hospital episodes complicated by acute kidney injury. (2020) - James, Benjamin; Sykes, Lynne; Flanagan, Emma; Sinha, Smeeta; Kalra, B Philip; Green, Darren
No abstract available